Religion on the Edge 2012
DOI: 10.1093/acprof:oso/9780199938629.003.0003
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Strong Program in the Sociology of Religion

Abstract: This chapter explores the issue of cultural autonomy as it relates to our portrayals of religion. First, it looks at the recent move toward a more robust view of religion and culture. Then it considers at some of the critiques of the idea of cultural autonomy that have taken place over the last few decades. Finally, it reviews some alternatives for understanding the causal impact of religious culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
2
23
0
1
Order By: Relevance
“…We found that scholars in the sociology of religion—as represented by content in JSSR and the Sociology of Religion —were preoccupied with parochial concerns. Notably, a study conducted concurrently by Smilde and May (2010) reported similar findings.…”
Section: Studies Of Western and Non‐western Regions In Mobilization (supporting
confidence: 54%
See 1 more Smart Citation
“…We found that scholars in the sociology of religion—as represented by content in JSSR and the Sociology of Religion —were preoccupied with parochial concerns. Notably, a study conducted concurrently by Smilde and May (2010) reported similar findings.…”
Section: Studies Of Western and Non‐western Regions In Mobilization (supporting
confidence: 54%
“…Moreover, there have been earnest calls by respected scholars of religion concerning the need to increase the study of other faiths (see Smith 2008). There are also scholars who are currently making serious efforts to “push” the field toward publishing a greater diversity of scholarship (see Smilde and May 2010). Like these scholars, I also believe that a greater diversity of scholarship within the sociology of religion would make the field stronger.…”
Section: Studies Of Western and Non‐western Regions In Mobilization (mentioning
confidence: 99%
“…A growing criticism of contemporary sociological theories about human action is that they emphasize rational, instrumental action much more than action guided by morals or ultimate concerns (Mooney, ; Gorski, ; Sayer, ; Smith, , ; Archer, ). Yet, even studies of culture, morality and religion still often adopt an instrumental and individualist view of human action (Smilde, ). For example, Swidler (2001; 1986) rightly rejects a Parsonian view of culture, in which human action is largely determined by society's shared values.…”
Section: Social Action and Relational Goodsmentioning
confidence: 99%
“…In her book Talk of Love , the object of her analysis consists of “the cultural resources themselves—the traditions, rituals, symbols and pieces of popular culture—that people drew on in thinking about love” (, p. 4). She argues that humans select from a repertoire of cultural practices to solve the daily problems that arise in social life, but she still does not examine what are the ends that people pursue (Smilde, ; Smith, ). Hence, Swidler's notion of cultural repertoires or culture as a tool‐kit still implicitly assumes that cultural activities are pursued as part of a strategy to attain other ends, leaving the nature of those ends unexplored.…”
Section: Social Action and Relational Goodsmentioning
confidence: 99%
“…Recent attention to the sociological study of religion has suggested a continued emphasis on religion in the United States, Protestantism, and Christianity to the exclusion of Eastern religion and regions of the world (Smilde and May 2010; Poulson and Campbell 2010). Poulson's response (this issue) to my “From the Editor” in the September 2010 issue declares that the social scientific study of religion not only continues to be parochial, but will likely remain parochial into the immediate future.…”
mentioning
confidence: 99%